ApCPEB4, a non-prion domain containing homolog of ApCPEB, is involved in the initiation of long-term facilitation. Issue 1 (December 2016) - Lee, Seung-Hee; Shim, Jaehoon; Cheong, Ye-Hwang; Choi, Sun-Lim; Jun, Yong-Woo; Lee, Sue-Hyun; Chae, Yeon-Su; Han, Jin-Hee; Lee, Yong-Seok; Lee, Jin-A; Lim, Chae-Seok; Si, Kausik; et al.
Abstract Two pharmacologically distinct types of local protein synthesis are required for synapse- specific long-term synaptic facilitation (LTF) inAplysia : one for initiation and the other for maintenance. ApCPEB, a rapamycin sensitive prion-like molecule regulates a form of local protein synthesis that is specifically required for the maintenance of the LTF. However, the molecular component of the local protein synthesis that is required for the initiation of LTF and that is sensitive to emetine is not known. Here, we identify a homolog of ApCPEB responsible for the initiation of LTF. ApCPEB4 which we have named after its mammalian CPEB4-like homolog lacks a prion-like domain, is responsive to 5-hydroxytryptamine, and is translated (but not transcribed) in an emetine-sensitive, rapamycin-insensitive, and PKA-dependent manner. The ApCPEB4 binds to different target RNAs than does ApCPEB. Knock-down of ApCPEB4 blocked the induction of LTF, whereas overexpression of ApCPEB4 reduces the threshold of the formation of LTF. Thus, our findings suggest that the two different forms of CPEBs play distinct roles in LTF; ApCPEB is required for maintenance of LTF, whereas the ApCPEB4, which lacks a prion-like domain, is required for the initiation of LTF.